2011
DOI: 10.1200/jco.2011.29.15_suppl.e16002
|View full text |Cite
|
Sign up to set email alerts
|

Parotid squamous cell carcinoma: Is it a primary or secondary?

Abstract: Background: To evaluate patients with parotid squamous cell carcinoma (SCC) to see is it a primary or metastatic and determine the outcome of patients who metastasis to the parotid. Patients and Methods: Fifty nine patients were identified with parotid SCC through the hospital database , patients' charts, imaging studies and computerized notes. Results: Fifty patients diagnosed as metastatic SCC of parotid lymph nodes. However, 9 patients diagnosed as primary. Forty seven patients with metastatic SCC treated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 6 publications
2
11
0
Order By: Relevance
“…A published independent study included less than 30 patients. In our PubMed database search over the last 30 years, we found only 10 articles, which included a total of 153 cases of pPSCC (1,3,5,(16)(17)(18)(19)(20)(21). Of all the included studies, only 3 reported on patient prognosis (1,3,21).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A published independent study included less than 30 patients. In our PubMed database search over the last 30 years, we found only 10 articles, which included a total of 153 cases of pPSCC (1,3,5,(16)(17)(18)(19)(20)(21). Of all the included studies, only 3 reported on patient prognosis (1,3,21).…”
Section: Discussionmentioning
confidence: 99%
“…Of all the included studies, only 3 reported on patient prognosis (1,3,21). The remainder did not analyze treatment results at all (5,9,10,(16)(17)(18)(19)(20)22) or did not distinguish between metastatic SCC and other histopathological parotid carcinomas (9,20,(22)(23)(24)(25)(26)(27)(28). One study evaluated the prognosis of SCC in a group of patients that combined parotid and submandibular glands (29).…”
Section: Discussionmentioning
confidence: 99%
“…This disease has been particularly understudied. One reason for this is its questionable etiology, with previous studies indicating that the majority of these cancers are metastases from primary cutaneous malignancies . This has led to the exclusion of this subtype from many analyses of treatments for salivary cancers .…”
Section: Introductionmentioning
confidence: 99%
“…One reason for this is its questionable etiology, with previous studies indicating that the majority of these cancers are metastases from primary cutaneous malignancies. 4,5 This has led to the exclusion of this subtype from many analyses of treatments for salivary cancers. [6][7][8][9] Unsurprisingly, there is a paucity of data about the outcomes associated with various adjuvant treatment strategies for salivary SCC despite the poor prognosis of these cancers, with some projecting 5-year survival at around 25%.…”
Section: Introductionmentioning
confidence: 99%
“…Salivary gland cancers have a large degree of histological heterogeneity, with over 20 identified malignant variants, the majority of which are non-squamous salivary cancers [11]. While salivary squamous cell carcinomas (SCC) can occur in the major salivary glands, many argue that the majority are metastases from cutaneous squamous cell carcinomas rather than primary salivary malignancies [12, 13]. This underlying biological difference between salivary gland cancers and upper aerodigestive tract malignancies may lead to different behavior and ECE status may not be as indicative of aggressiveness for salivary gland malignancies as it is for upper aerodigestive tract cancers.…”
Section: Introductionmentioning
confidence: 99%